Analisis Pengaruh Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Rawat Jalan RSUD Raja Ahmad Tabib Provinsi Kepulauan Riau - Tama, Lora Patal; Purwanto, Purwanto; Wulandari, Florentina Ratih (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study examines the impact of healthcare service quality on outpatient satisfaction at RSUD Raja Ahmad Tabib, Riau Islands Province. The research is driven by the increasing recognition that high-quality healthcare services are essential for ensuring patient satisfaction, which is a critical measure of a hospital's overall performance and reputation. The study seeks to determine the degree to which service quality influences the satisfaction levels of outpatients. A quantitative research approach was adopted, involving the distribution of surveys to outpatients, with data analyzed through simple linear regression to assess the correlation. The results reveal a significant and positive relationship between the quality of healthcare services and patient satisfaction, indicating that enhancements in service delivery lead to greater patient contentment. The findings underscore the necessity of prioritizing service quality improvements as a strategic initiative to boost patient satisfaction and, consequently, the hospital's success.